Changes in summer sea ice, albedo, and portioning of surface solar radiation in the Pacific sector of Arctic Ocean during 1982–2009. Issue 8 (5th August 2016) - Lei, Ruibo; Tian‐Kunze, Xiangshan; Leppäranta, Matti; Wang, Jia; Kaleschke, Lars; Zhang, Zhanhai
Abstract: SSM/I sea ice concentration and CLARA black‐sky composite albedo were used to estimate sea ice albedo in the region 70°N–82°N, 130°W–180°W. The long‐term trends and seasonal evolutions of ice concentration, composite albedo, and ice albedo were then obtained. In July–August 1982–2009, the linear trend of the composite albedo and the ice albedo was −0.069 and −0.046 units per decade, respectively. During 1 June to 19 August, melting of sea ice resulted in an increase of solar heat input to the ice‐ocean system by 282 MJ·m −2 from 1982 to 2009. However, because of the counter‐balancing effects of the loss of sea ice area and the enhanced ice surface melting, the trend of solar heat input to the ice was insignificant. The summer evolution of ice albedo matched the ice surface melting and ponding well at basin scale. The ice albedo showed a large difference between the multiyear and first‐year ice because the latter melted completely by the end of a melt season. At the SHEBA geolocations, a distinct change in the ice albedo has occurred since 2007, because most of the multiyear ice has been replaced by first‐year ice. A positive polarity in the Arctic Dipole Anomaly could be partly responsible for the rapid loss of summer ice within the study region in the recent years by bringing warmer air masses from the south and advecting more ice toward the north. Both these effects would enhance ice‐albedo feedback. Key Points: A distinct change in the seasonal evolution of ice albedo at the SHEBA geolocations has occurred since 2007 Summer evolution of ice albedo matched ice surface melting and ponding well at basin scale A positive Arctic Dipole Anomaly might enhance the ice‐albedo feedback in the Pacific sector of Arctic Ocean